2016
DOI: 10.2217/pgs-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitamin D Receptor Gene Polymorphisms, Cardiovascular Risk Factors and Adiponectin in a Healthy Young Population

Abstract: Our study demonstrated a gender-specific difference between VDR SNPs and various cardiovascular risk factors and adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
(30 reference statements)
0
22
1
Order By: Relevance
“…The males carrying the AA genotype of BsmI had a 2.63-fold higher risk of FMF (OR: 2.63; 95% CI: 1.12-6.01) compared to the males carrying the GG or AG genotypes. This finding is not in agreement with the results of Kizildag et al [29], but several other studies reported sex-related differences in the distribution of BsmI genotypes [30][31][32]. For example, Bodoki et al [30] showed significantly different distributions of BsmI genotypes between male and female patients with idiopathic inflammatory myopathy [30].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The males carrying the AA genotype of BsmI had a 2.63-fold higher risk of FMF (OR: 2.63; 95% CI: 1.12-6.01) compared to the males carrying the GG or AG genotypes. This finding is not in agreement with the results of Kizildag et al [29], but several other studies reported sex-related differences in the distribution of BsmI genotypes [30][31][32]. For example, Bodoki et al [30] showed significantly different distributions of BsmI genotypes between male and female patients with idiopathic inflammatory myopathy [30].…”
Section: Discussioncontrasting
confidence: 55%
“…Different genotype frequencies of BsmI have also been observed between male and female patients with Graves' disease [31]. Finally, the AA genotype of BsmI polymorphism has been associated with higher body mass index, higher waist circumference, and lower adiponectin levels in randomly selected healthy men [32]. In the study of Dogan et al [3], no significant difference was observed between male and female patients with FMF in the rate of heterozygous and homozygous mutations of MEFV gene [3].…”
Section: Discussionmentioning
confidence: 98%
“…This study revealed no significant difference of vitamin D status between females and males This is in conformity with results of a systematic review of vitamin D status in populations worldwide which did not reveal any substantial gender-related differences in vitamin D status, except in the Middle East and Asia, probably due to the dressing code of females in these regions [ 24 , 25 ]. Contrarily, a study in Lebanon revealed that females had significantly higher vitamin D levels than males [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequences were obtained from UCSC or Genbank databases. The primers used for the study, which were ApaI, Cdx2, BmsI, TaqI, and FokI SNPs, were the same as those used respectively by Hajj et al [28]. The PCR products were verified using 1% agarose gel con-taining SYBR ® Safe (Life Technologies, CA, USA).…”
Section: Rflp-pcrmentioning
confidence: 99%